One Step Ahead—Attention Control Capabilities at Baseline Are Associated With the Effectiveness of the Attention Training Technique - Heitland, Ivo; Barth, Vincent; Winter, Lotta; Jahn, Niklas; Burak, Alev; Sinke, Christopher; Krüger, Tillmann H. C.; Kahl, Kai G. (Frontiers in Psychology, 2020)
Background Attentional control has been observed to play an important role in affective disorders by impacting information processing, the ability to exert top–down control in response to distracting stimuli, and by affecting emotional regulation. Prior studies demonstrated an association between attentional control and response to psychotherapy, thereby identifying attentional control as an interesting prognostic pre-treatment factor. Improving attentional control and flexibility is a cornerstone in metacognitive therapy (MCT), which is trained by the use of the Attentional Training Technique (ATT). However, as of yet, it remains unclear if pre-treatment attentional control is related to the effect of ATT. Methods An aggregated sample of 139 healthy participants [study 1: 85 participants, mean age 23.7 years, previously published (Barth et al., 2019); study 2: 54 participants, mean age 33.7 years, not previously published] performed an attentional performance test battery before and after applying ATT. Before ATT was administered, attentional control was measured using a well-established self-report instrument, i.e., the Attentional Control Scale (ACS; Derryberry and Reed, 2002). ATT was given in 2, 4, or 15 doses and compared to sham ATT. The test battery comprised a selection of established neurocognitive tasks: emotional dot probe, Stroop, 2-back, and dichotic listening. Results Sham ATT showed no interaction with ACS score on performance outcome in all tests. At four doses of ATT, ACS score was associated with training response, i.e., subjects with high self-reported attentional control before training showed the largest improvements post-training (all P-values <0.05; see Figure 3). At 2 and 15 doses of ATT, the ACS score was unrelated to training response. Conclusion This is a first attempt in understanding the optimal dosage in which ATT should be administered dependent on the individual characteristics of each subject pre-training. The current data suggest self-reported attentional control pre-training as a marker to determine an optimal individual ATT training profile. Future studies should investigate if other domains of metacognitions also interact with training outcome and evaluate the extent to which this relationship transfers to clinical samples. If successful, assessing attentional control prior to treatment in clinical samples could be of use regarding personalized therapy plans and treatment outcome.